Task Analysis to Improve Eating Ability for Down Syndrome Children - Sonya, Neldita; Nurul Aien Abd Aziz; Yusnimar; Elina, Darta (International Journal of Pedagogy, 2024)
Research early from problems which is the ability to eat find at class of 1 CI SLB Fan Redha Padang, in subject specifically the ability to eat. On building self-esteem, especially aspects of eating. When children eat lunch at school, children are often fed by parents, teachers and friends of children, so that children always rely on those who are nearby in the activities of the child's independence. So we need a method to solve this problems, one of them is of Task Analysis.This research use experiment type with single subject and AB design. Subject of this Research is a student at class of 1 CI SLB Fan Redha Padang. Data's collect in the form of deed test through perception/observation, and data collecting appliance in the form of instrument The test counted 15 items . Acquisition of data analyzed to use analysis visual data techniques.